Prevalence and clinical outcome of hepatic haemangioma with specific reference to the risk of rupture: A large retrospective cross-sectional study. Issue 3 (March 2016) - Mocchegiani, Federico; Vincenzi, Paolo; Coletta, Martina; Agostini, Andrea; Marzioni, Marco; Baroni, Gianluca Svegliati; Giovagnoni, Andrea; Guerrieri, Mario; Marmorale, Cristina; Risaliti, Andrea; Vivarelli, Marco
Abstract: Background: Prevalence and incidence of hepatic haemangioma are estimated from autopsy series only. Although benign and generally asymptomatic, hepatic haemangioma can cause serious complications. Aims: The aim of the study was to assess the prevalence of hepatic haemangioma and to attempt to quantify the risk of major complications such as spontaneous rupture. Methods: We retrospectively analyzed the radiology database of a Regional University Hospital over a 7-year period: the radiological records of 83, 181 patients who had an abdominal computed tomography or magnetic resonance scan were reviewed. Diagnoses made at imaging were reviewed and related to clinical course. Results: Hepatic haemangioma was diagnosed in 2071 patients (2.5% prevalence). In 226 patients (10.9%), haemangioma had diameter of 4 cm or more (giant haemangioma). The risk of bleeding was assessed on patients without concomitant malignancies. Spontaneous bleeding occurred in 5/1067 patients (0.47%). All 5 patients had giant haemangioma: 4 had exophytic lesions and presented with haemoperitoneum; 1 with centrally located tumour experienced intrahepatic bleeding. Conclusion: Giant haemangiomas have a low but relevant risk of rupture (3.2% in this series), particularly when peripherally located and exophytic. Surgery might be considered in these cases.